Single-step primary open-angle glaucoma and complicated cataract surgery using modified technique of stainless steel Glaucoma Filtration Device implantation - I. L Bessonov; J. A. Gusev; V. N. Trubilin; S. M. Makkaeva (Oftalʹmologiâ, 2014)
Purpose: To analyze the efficacy of novel technique of primary open-angle glaucoma (POAG) and complicated cataract surgery that combines phacoemulsification and modified stainless steel Glaucoma Filtration Device implantation.Methods: 34 patients (38 eyes) with POAG and complicated cataract were included in the study. Phacoemulsification with Glaucoma Filtration Device implantation using improved technique (i.e., with additional collagen glaucoma drainage implantation and posterior scleral implantation) was performed.Results: Following phacoemulsification with Glaucoma Filtration Device implantation using modified technique, IOP was decreased by 43 % in a month and remains stable in a year while visual acuity improved almost 5 times in a year.Conclusion: Phacoemulsification with Glaucoma Filtration Device implantation using modified technique provides adequate IOP reduction and highest possible functional results in early and late post-op period.